The fear of goods from Hesiod to Adam Smith - Perrotta, Cosimo, 1942- (Routledge studies in the history of economics ;, 2004)
This work explores the changing place of consumption as a source of investment in production and growth within economic writings from ancient history to the present. This project is carried out with great skill, vigour and originality and will help to bring consumption studies to the mainstream of economic thought.